Emergent Spatio-temporal Dimensions of the City : Habitus and Urban Rhythms - Neuhaus, Fabian (Springer International Publishing : Imprint: Springer, 2015)
This book focuses on the creation of space as an activity. The argument draws not only on aspects of movement in time, but also on a cultural and specifically social context influencing the creation of the spatial habitus. The book reconsiders existing theories of time and space in the field of urban planning and develops an updated account of spatial activity, experience and space-making. Recent developments in spatial practice, specifically related to new technologies, make this an important and timely task. Integrating spatial-temporal dynamics into the way we think about cities aids the implementation of sustainable forms of urban planning. The study is composed of two different case studies. One case is based on fieldwork tracking individual movement using GPS, the other case utilises data mined from Twitter. One of the key elements in the conclusion to this book is the definition of temporality as a status rather than a transition. It is argued that through repetitive practices as habitus, time has presence and agency in our everyday lives. This book is based on the work undertaken for a PhD at the Centre for Advanced Spatial Analysis and was and accepted as thesis by University College London in 2013.